A practitioner`s guide to identifying, assessing, and managing gut issues in athletes - Costa, R. J. S.; Gaskell, S. K. (International Journal of Sports Medicine, 2026)
Exercise-associated gastrointestinal symptoms stemming from exercise-induced gastrointestinal syndrome are a common feature of sports participation. Exercise-associated gastrointestinal symptoms have the potential to directly impair sports performance or could indicate something more sinister warranting medical attention. Managing the underlying pathophysiological pathways of exercise-induced gastrointestinal syndrome is key to reducing exercise-associated gastrointestinal symptoms in athletes during their sporting activities. Recent advancements in exercise gastroenterology have enhanced the understanding of pathophysiology, assessment methodologies, prevention and management strategies. The current narrative review aims to provide a professional practice guide for the identification, assessment, intervention, and monitoring of exercise-induced gastrointestinal syndrome and exercise-associated gastrointestinal symptoms. A referral pathway and a four-phase approach to athlete support have been proposed. The athlete support pathway components include initial clinical assessment, gastrointestinal assessment during exercise, implementation of evidenced-informed prevention or management strategies based on the gastrointestinal assessment during exercise data interpretation, and ongoing monitoring and adjustment in real-world settings. This structured approach has been shown to reduce exercise-associated gastrointestinal symptoms and potentially mitigate underlying medical risks arising from exercise-induced gastrointestinal syndrome.